2021
DOI: 10.4067/s0718-48672021000100089
|View full text |Cite
|
Sign up to set email alerts
|

Desinformación Y Fact-Checking en Las Elecciones Uruguayas De 2019. El Caso De Verificado Uruguay

Abstract: ResumenEl objetivo de esta investigación es estudiar los procesos de desinformación que circularon durante las elecciones presidenciales uruguayas de 2019. Para ello, se ha examinado el trabajo realizado por el proyecto colaborativo de fact-checking Verificado Uruguay. Nuestra investigación establece una tipología de rumores políticos que se propagaron en esta campaña y pretende apuntar su origen y sus motivaciones. Asimismo, demuestra queaunque hay narrativas regionales-los contextos locales hacen que no sea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…However, the results of the research showed that disinformation was distributed equally between social networks sources and the political candidates in an identical percentage of cases (40.9%). In that sense, the research is close to what is argued by Carlson (2020) and moves away from Molina and Magallón's (2021) study on the 2019 Uruguayan presidential election and from the results of Paniagua et al (2020) regarding the main sources of disinformation of the 2019 Spanish general election. Consequently, the first hypothesis of the research ("H1: The disinformation generated during the 2020 US presidential election came primarily from social networks sources") would be refuted by the reported results.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…However, the results of the research showed that disinformation was distributed equally between social networks sources and the political candidates in an identical percentage of cases (40.9%). In that sense, the research is close to what is argued by Carlson (2020) and moves away from Molina and Magallón's (2021) study on the 2019 Uruguayan presidential election and from the results of Paniagua et al (2020) regarding the main sources of disinformation of the 2019 Spanish general election. Consequently, the first hypothesis of the research ("H1: The disinformation generated during the 2020 US presidential election came primarily from social networks sources") would be refuted by the reported results.…”
Section: Discussionsupporting
confidence: 64%
“…Only a small number came from websites identified as well-known disinformation sites, while the rest came from partisan or satirical websites. Molina and Magallón (2021) also found in their study on the 2019 presidential election in Uruguay that the channel through which the greatest volume of disinformation was distributed was social networks (Facebook reached 44% above Twitter (2.9%) and WhatsApp (19.6%); the three of them represented 86.6% of the total disinformation).…”
Section: Channels For Disinformationmentioning
confidence: 92%
See 2 more Smart Citations
“…However, in addition to this is the need to introduce alternative views in the academic field, complementary to the prevailing "Global North" (Mitchelstein & Boczkowski, 2021;Valenzuela et al, 2019). This is because, despite being significant, Latin-American fact-checking initiatives have not yet been adequately studied (Molina-Cañabate & Magallón-Rosa, 2021). In this research, we decided to approach Ibero-America (Latin American countries, plus Spain and Portugal) This is because as well as the cultural and linguistic ties binding the countries under this name, there is a large amount of collaboration between Latin America and Iberian fact-checkers.…”
Section: Fact-checking In Ibero-americamentioning
confidence: 99%